Modular instruction in humanities utilizing bicol materials: It's effects on students' performance of camarines sur polytechnic colleges - Tataro, Marietta Almonte (San Miguel, Iriga City: University of Saint Anthony, 2000)
Modular instruction in humanities utilizing bicol materials: its effects on students' performance of camarines sur polytechnic colleges.
Includes bibliographical references.
English